Feminist Conversations on Peace - Smith, Sarah; Yoshida, Keina (Bristol University Press, 2022)
EPUB and EPDF available Open Access under CC-BY-NC-ND licence. What is feminist peace? How can we advocate for peace from patriarchy? What do women, globally, advocate for when they use the term 'peace'? This edited collection brings together conversations across borders and boundaries to explore plural, intersectional and interdisciplinary concepts of feminist peace. The book includes contributions from a geographically diverse range of scholars, judges, practitioners and activists, and the chapters cut across themes of movement building and resistance and explore the limits of institutionalized peacebuilding. The chapters deal with a range of issues, such as environmental degradation, militarization, online violence and arms spending. Offering a resource to advance theoretical development and to advocate for policy change, this book transcends traditional approaches to the study of peace and security and embraces diverse voices and perspectives which are absent in both academic and policy spaces.